2019
DOI: 10.1200/jco.2019.37.15_suppl.9098
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of bemcentinib (BGB324), a first-in-class highly selective AXL inhibitor, with pembrolizumab in pts with advanced NSCLC: OS for stage I and preliminary stage II efficacy.

Abstract: 9098 Background: AXL is an RTK implicated in epithelial-to-mesenchymal transition and as a resistance mechanism to multiple therapies including anti-PD1. Bemcentinib (BGB324) is a first-in-class, oral, highly selective and potent AXL inhibitor which has been demonstrated to enhance anti-PD1 therapy in the pre-clinical setting. Methods: This is a Phase II single-arm, two-Stage study with bemcentinib (200mg/d) and pembrolizumab (200 mg/q3wk) for previously treated, IO naïve pts (n = 48 in total) with Stage IV l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…2 right panel). Indeed, in a recent clinical trial NCT03184571, the combination of AXL inhibitor and anti-PD1 has shown promising efficacy among AXL-positive non-small cell lung cancer patients [10]. Hence, this module can prioritize genes with the best potential for developing combination immunotherapies.…”
Section: Gene Set Prioritization Modulementioning
confidence: 99%
“…2 right panel). Indeed, in a recent clinical trial NCT03184571, the combination of AXL inhibitor and anti-PD1 has shown promising efficacy among AXL-positive non-small cell lung cancer patients [10]. Hence, this module can prioritize genes with the best potential for developing combination immunotherapies.…”
Section: Gene Set Prioritization Modulementioning
confidence: 99%
“…The metabolic changes associated with M1/M2 polarization may also regulate activation state (196,197). Much like the distinct glutaminase-dependent differentiations of Th17 and Th1 T cells to regulate the immune response (198), direct metabolic changes in macrophages, or the output of altered metabolism, can affect M1/M2 polarization.…”
Section: Manipulating Macrophage Metabolism To Increase M1 Polarizationmentioning
confidence: 99%
“…For AXL-positive patients, the ORR was 40%. The median PFS was 4.0 months and 5.9 months for AXL-positive patients [70].…”
Section: Axl Kinase Inhibitormentioning
confidence: 99%